Perkembangan Kognitif Anak Usia Dini Penyandang Disleksia: Studi Kasus Pada Lembaga Pendidikan Di Indonesia - Lilif Muallifatul Khorida Filasofa; Miswati Miswati (FITK UIN Walisongo Semarang, 2021)
Dyslexia is a disorder of the nervous system that is characterized by difficulty recognizing words both reading, spelling, understanding symbols and distinguishing letters. Dyslexic children experience barriers to cognitive development. Children tend to be slow in thinking and hard to understand things like counting, analyzing and understanding words. Some factors that cause children to experience dyslexia are educational, psychological and biological factors. But the main thing is neubiological factors or the brain. This is due to poor connectivity in the function of parts of the brain, namely the brocas, frontal lobe and cortex. Therefore parents or teachers need to implement appropriate strategies or handling methods so that the child's cognitive abilities can develop properly.